EKSTRAKSI DAN DETEKSI FITOKIMIA KENIKIR (Cosmos caudatus Kunth.) ASAL PANJANG UTARA, LAMPUNG - Nida Lidya Susanti; Devi Eka Lestari; Rohimatul Anwar (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2024)
Kenikir (Cosmos caudatus Kunth.) is a plant species with many benefits. One of the benefits is that the Indonesian citizen uses it as a medicinal ingredient. This study aims to determine the phytochemical content of kenikir leaves (Cosmos caudatus Kunth.) obtained from farmers in Panjang Utara region, Bandar Lampung, Lampung. The method used is maceration and phytochemical testing where the kenikir leaves are sorted and washed then air-dried and homogenized using a homogenizer to become powder. Kenikir leaf powder is extracted using the maceration method with Ethanol 70% and then tested for phytochemical content of saponins, steroids, terpenoids, tannins, alkaloids, flavonoids, and phenolics. The results of the study showed that kenikir leaves do not contain steroid but contain saponin, terpenoid, tannin, alkaloid, flavonoids, and phenolic compounds that have the potential to be used for human health such as anticancer, antioxidant, antibacterial, and anti-inflammatory. The highest phytochemicals in kenikir leaf extract are saponin and flavonoid. Both saponin and flavonoid have the potential as antimicrobials.